A Historical Institutionalist Analysis of the Evolution of South Africa's Municipal Electricity Sector within the Broader Electricity Supply Industry - Covary, Theodore (Energy Research Centre, 2020)
This study has been partly inspired by the fact that historical narratives on the evolution of the South African Electricity Supply Industry (ESI), have for the most part focused on the national vertically integrated utility, Eskom; with far less attention being paid to the role that the municipal electricity undertakings (MEU's) have, and continue to, play. Indeed, this is somewhat surprising if one considers that MEU's began operating more than 20 years before Eskom's 1923 formation; and perhaps this lack of focus on MEU's is compounded by Eskom's operational crisis from 2006 (threatening its ongoing viability), which has overshadowed the perilous situation that MEU's have found themselves in. The research thus has two objectives. The first is to provide a detailed historical account of the role of MEU's and their contribution to the country's ESI from their genesis; while demonstrating the linkages between Eskom, MEU's and the three tiers of government. The second then examines how from the formation of the Union (1910), two fundamental but diametrically opposing objectives continue to prevail: 1) An over-burdened, financially ‘self-sufficient', local government, whose limited scope to collect revenue means electricity surpluses must be maximised to cross-subsidise its operations; and, 2) A vertically integrated utility, mandated to generate electricity at the lowest unit price, so as to provide the energy intensive economy with a competitive advantage. These contradictions, which have endured for many decades, reached fever pitch in the last 20 years, contributing significantly to the demise of ESI reforms initiated in 2000 and abandoned in 2010. Simultaneously, they have worsened the crisis of local government, which is constitutionally mandated to deliver basic services to its constituents, whose failure to do so, in many instances now threatens national government legitimacy at the most fundamental level. Within this context, the research, (based on the premise that history and institutions matter), employs the theoretical framework of new institutionalism, as applied through the lens of historical institutionalism (HI). Here, application of HI's core tenets revolves around identifying and explaining the critical junctures which create path dependency and institutional lock-in, while also accounting for incremental change which undoubtedly exists over a 120-year period. However, the unjust social and economic history of the country, where political decisions (pre and post-apartheid) have had a disproportional impact on state entities, requires closer scrutiny. For this, a detailed conceptual framework is employed to disentangle the complex relationship that has developed between the three tiers of government and their respective interacting powers. Ultimately, in delivering a detailed historiography of municipal electricity supply, the research posits that the ESI requires deeper fundamental reform than envisaged in 2000; and that most importantly, this must take cognisance of the extent to which MEU's are embedded within local government. This, the research believes, will increase the likelihood of local government participation and acceptance; perhaps pointing to an as yet unexplored path forward out of the South African ESI's current quandary.